2019
DOI: 10.1088/2043-6254/ab1b79
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic iron oxide/graphene oxide nanocomposites for removal of cadmium ions from water

Abstract: In this study, magnetic iron oxide/graphene oxide (Fe 3 O 4 /GO) nanocomposites were developed for removal of cadmium ions (Cd 2+ ) from water, which could be effectively separated from the solution owing to its superparamagnetic property. The Fe 3 O 4 /GO nanocomposites were fabricated by coprecipitation method with different precursor ratios of 8:1, 4:1, 2:1, and 1:1. It was found that the suitable ratio of Fe 3 O 4 /GO for Cd 2+ ions adsorption was 4:1 (FG2). The effects of contact time, pH, and metal initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…This is also equivalent to the XRD data for Fe3O4 cubic phase with a face-centred cubic (fcc) structure. [17] The TEM image in figure 2a-2b revealed that GO and SGO contained two-dimensional monolayer with many wrinkles on their surfaces because of the interaction of π-π bonding or among oxygencontaining group, [13] but for Fe3O4/SGO (figure 2c-2d), the attendance of black points in above images confirmed the appearance of Fe3O4 NPs distributing among the GO layers with average size 12.53±1.75 nm as show in figure 2e. Moreover, figure 2c pointed out that TEM image of Fe3O4/SGO also had wrinkles as seen in figure 2a-2b, since the Fe3O4 NPs had connected to GO surface, therefore strengthened the magnetic property and also widen the distance among GO layers.…”
Section: Characterization Of Catalyticmentioning
confidence: 83%
See 1 more Smart Citation
“…This is also equivalent to the XRD data for Fe3O4 cubic phase with a face-centred cubic (fcc) structure. [17] The TEM image in figure 2a-2b revealed that GO and SGO contained two-dimensional monolayer with many wrinkles on their surfaces because of the interaction of π-π bonding or among oxygencontaining group, [13] but for Fe3O4/SGO (figure 2c-2d), the attendance of black points in above images confirmed the appearance of Fe3O4 NPs distributing among the GO layers with average size 12.53±1.75 nm as show in figure 2e. Moreover, figure 2c pointed out that TEM image of Fe3O4/SGO also had wrinkles as seen in figure 2a-2b, since the Fe3O4 NPs had connected to GO surface, therefore strengthened the magnetic property and also widen the distance among GO layers.…”
Section: Characterization Of Catalyticmentioning
confidence: 83%
“…Moreover, the significant smaller peak intensity of Fe3O4/SGO material than two others have proved the association of Fe3O4 NPs and oxygen-containing group on pristine GO plate. [13] The XRD pattern in of GO in figure 1b showed peak at low angle 2θ = 9.47 o with dspace = 9.33 Å. In graphite, the inter layer separation was just about 3.33 Å, [14] but with the existence of oxygencontaining groups on graphite sheet, the C-C bonding broke down in the oxidation process and the interplanar distance was increased and lead to lower the value of 2θ.…”
Section: Characterization Of Catalyticmentioning
confidence: 99%
“…A magnetic Fe 3 O 4 /graphene oxide nanocomposite material was synthzed and used for Pb 2+ removal from water samples by Thy et al (2020). The optimum Pb 2+ ions adsorption onto nanocomposite material conditions were performed by RSM combined with Box-Behnken design approach.…”
Section: Rsm Statistical Analysis and Model Ttingmentioning
confidence: 99%
“… 4 Graphene oxide was used as the support to magnetic iron oxide to form nanocomposite material, the material can separate effectively Cd(II) ions in aqueous solution. 5 Beside that, TiO 2 –SiO 2 -mixed oxide nanoparticles were developed as a heterogeneous photocatalysis, the material showed significantly higher methylene blue removal efficiency in comparison with that of the commercial TiO 2 material. 6 …”
Section: Introductionmentioning
confidence: 98%